2014
DOI: 10.1007/s12098-014-1661-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile in Neonates and its Relation with Birth Weight and Gestational Age

Abstract: This study was undertaken to compare lipid profile of small for gestational age (SGA) and appropriate for gestational age (AGA) neonates. A total of 103 neonates were included; of which 63 were AGA and 40 SGA. Venous blood (2 ml) was obtained 2 h after the previous feed between 8 and 10 am on Day 3 or Day 4 of life and lipid profile was done. In AGA neonates, mean TC (total cholesterol), LDL (low density lipoprotein cholesterol), HDL (high density lipoprotein cholesterol) and triglycerides were 103.92 ± 47.79,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…In addition, Ramaraj et al studied the entire lipid profile in AGA and SGA neonates, and they found that total cholesterol and LDL were significantly lower in SGA neonates (p < 0.05) which was in accordance with our results. 21,22 Regarding the correlation between the maternal serum lipid profile and the neonatal birth weight, it had been previously shown that the maternal concentration of TG in the third trimester is a stronger predictor of birth weight than glucose parameters. 23 Ghiasi et al found a positive correlation between the maternal serum TG level and the neonatal crown-heel length, as well as the birth weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Ramaraj et al studied the entire lipid profile in AGA and SGA neonates, and they found that total cholesterol and LDL were significantly lower in SGA neonates (p < 0.05) which was in accordance with our results. 21,22 Regarding the correlation between the maternal serum lipid profile and the neonatal birth weight, it had been previously shown that the maternal concentration of TG in the third trimester is a stronger predictor of birth weight than glucose parameters. 23 Ghiasi et al found a positive correlation between the maternal serum TG level and the neonatal crown-heel length, as well as the birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ramaraj et al studied the entire lipid profile in AGA and SGA neonates, and they found that total cholesterol and LDL were significantly lower in SGA neonates ( p < 0.05) which was in accordance with our results. 21 22…”
Section: Discussionmentioning
confidence: 99%
“…From the lipid profiles obtained in this study and based on evidence from international studies, like Adamkin 19 , Ghaemi et al 22 Ramaraj et al 23 , it is identified that these PT can be considered as at risk for cardiovascular impairment and development of MS throughout their lives.…”
mentioning
confidence: 76%
“…High triglyceride concentrations in PT increase the risk of developing cardiovascular diseases in the future; therefore, we must invest in actions that promote adequate nutrition for these children from birth to minimize the risks of future chronic diseases 23 . Moreover, this evidence indicates that during the follow-up of this group in the first years of life, the evolution of the lipid profile should be followed, since at 2 years of age the child will have the cholesterol levels he or she will maintain in the first 10 years of life 24 .…”
mentioning
confidence: 99%
“…[ 8 ] The average lipid parameters reported from the Western population in the neonates and from Indian populations are widely different. The data from one Indian study shows that the average total cholesterol, HDL-cholesterol, LDL-cholesterol, and triglycerides measured on day 3 or 4 were (total cholesterol 103.92 ± 47.79 mg/dl, triglycerides 187.62 ± 144.44 mg/dl, HDL-cholesterol 23.35 ± 11.41 mg/dl, and LDL-cholesterol 51.70 ± 23.03 mg/dl)[ 9 ] is nearly twice as higher as measured from a similar Western population measured just after birth (total cholesterol 53.9 ± 14.6 mg/dl, triglycerides 29.5 ± 16.0 mg/dl, HDL-cholesterol 21.9 ± 6.3 mg/dl, and LDL-cholesterol 26.2 ± 10.1 mg/dl). [ 10 ] Similar trends were also noted while comparing another Indian population data versus an Western population data.…”
Section: Discussionmentioning
confidence: 99%